FABRICATION OF COPPER NANOPARTICLE USING CATHARANTHUS ROSEUS BY GREEN SYNTHESIS AND ITS ANTIBACTERIAL ACTIVITY - MARY VERGHEESE. T; PRINCE JACOB RAJ. J; KIRAN VISHAL; ANSHA ELIZABETH MAMMEN RINTO JOSE; EBENEZER JOSHUA. J (International Journal of Pharma and Bio Sciences, 2015)
In the present study, fabrication of copper nanoparticle is achieved by Green Synthesis using the aqueous leaf extract of Catharanthus roseus. Catharanthus roseus is an evergreen shrub. The plant has various medicinal properties and used to make anti-carcinogenic and anti-diabetic drugs. Copper nanoparticle also exhibit antibacterial activity. The reduction of copper salt using the aqueous leaf extract resulted in the formation of copper nanoparticle. Immediate colour change was observed which indicates the formation of copper nanoparticle. It is a single pot synthesis, because the plant extracts functions as both a reducing and also as a capping agent. The fabricated nanoparticle is characterized using UV -Vis spectrophotometer. The UV-Vis absorbance maximum confirms the presence of copper nanoparticle. FT-IR technique is also used for characterization. SEM studies show that the size of nanoparticle ranges between 40nm – 47nm which looks like coral reef. The antibacterial activity of copper nanoparticle is also studied. This method proves to be cost effective, environment friendly and can be used in the synthesis of copper nanoparticles compared to other chemical reduction methods.